1988
DOI: 10.1029/rs023i005p00831
|View full text |Cite
|
Sign up to set email alerts
|

The real height analysis of ionograms: A generalized formulation

Abstract: A new procedure is described for the calculation of real height profiles from ionospheric W(f) records. The equations are formulated in a way which can reproduce all current methods of analysis, and provide many powerful extensions. For general use a sixth-order overlapping polynomial analysis is recommended, with real height sections determined by a least squares fit to real and virtual height data. Coefficients can also be obtained for single polynomials fitted separately to each ionospheric layer. All metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 26 publications
0
84
0
Order By: Relevance
“…All the above indicate that additional tests are required in order to extract safe conclusions on the potentiality of the proposed method in accommodating routine Digisonde profiles. These tests should include the assessment of the method with manually scaled Digisonde profiles and/or the implementation of alternative scaling techniques, as for example POLAN software (Titheridge 1988).…”
Section: Calculatedmentioning
confidence: 99%
“…All the above indicate that additional tests are required in order to extract safe conclusions on the potentiality of the proposed method in accommodating routine Digisonde profiles. These tests should include the assessment of the method with manually scaled Digisonde profiles and/or the implementation of alternative scaling techniques, as for example POLAN software (Titheridge 1988).…”
Section: Calculatedmentioning
confidence: 99%
“…The EOF-based inversion is developed from the traditional polynomial analysis of Titheridge (1961Titheridge ( , 1967aTitheridge ( , b, 1969Titheridge ( , 1975Titheridge ( , 1988 and Huang and Reinisch (1982) where the prior polynomials, e.g., Taylor polynomials or shifted Chebyshev polynomials, have now been replaced with empirical orthogonal functions (EOFs). The new technique has been applied here to the data processing of the MARSIS ionograms, with EOFs retrieved from the MGS radio occultation measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the lamination methods are now rarely used in practice. Titheridge (1961Titheridge ( , 1967aTitheridge ( , b, 1969Titheridge ( , 1975Titheridge ( , 1988 proposed a model-fitting method, or polynomial analysis in which the curve of true height vs. plasma frequency, h( f p ), is represented as a single or overlap-ping polynomial(s). Huang and Reinisch (1982) further developed the polynomial analysis by replacing Titheridge's Taylor polynomials with shifted Chebyshev polynomials, and applied it to the data processing of ISIS topside ionograms.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a premature truncation of the scaled F2 trace were made by earlier versions of the autoscaling software, caused by echo trace gaps due to restricted frequency bands and/or bands of strong interference (Reinisch et al, 2005). Also, a comparison of the true-height electron density profiles inverted from ionograms using the POLAN (Titheridge, 1988) and NHPC (Reinisch et al, 2005) methods showed significant systematic differences (Sauli et al, 2007). Such differences can be explained with the differences in the underlying ionospheric profilers that are used.…”
Section: Introductionmentioning
confidence: 99%